The Influence of Longitudinal Force on the Internal Force Distribution and Deformation Coordination Mechanism for Segment Lining - Cao Songyu; Feng Kun; Liu Xun; He Chuan; Xiao Mingqing (Advances in Civil Engineering)
A series of local prototype tests are conducted on the Sutong GIL (Gas-Insulated Line) and Shiziyang Tunnel. These tests investigate the redistribution law of segment deformation and the bending moment during construction. The results reveal that the transfer ability of deformation and the bending moment improve with an increase in the longitudinal force. Stage characteristics are observed for the effect of the longitudinal force on the opening of the circumferential joints. Segments are fully contacted for the circumferential joints when the joint opening is not observed. The frictions between the segments are the key factors for the bending moment and segment deformation control. The opening of the circumferential joint with an increase in the joint opening then becomes the primary control factor. The transfer ability becomes stable when the load continues increasing after mortise and tenon contact. Better transfer ability occurs with a general segment with four pairs of mortises and tenons. This was presented as a smaller value of an increasing rate and the stable magnitude of the joint opening. From the perspective of practical engineering, mortises and tenons can be added to the vault to increase the load and deformation transfer ability of the general segment after the loss of the longitudinal force.